Analisis Makna Semantik pada Puisi Bahasa Sasak “Presean” Karya Syaiful Bahri - Zulkarnaen, Lalu Purnama; Sukarni, Sri; Akmaluddin, Akmaluddin (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to analyze the Sasak poem entitled "Presean" by Syaiful Bahri using a semantic study that includes lexical meaning, grammatical meaning, referential meaning, and figurative meaning. The method used in this study is a descriptive method. The research data is in the form of a Sasak poem text "Presean" by Syaiful Bahri. The data analysis technique includes three stages, namely data reduction, data presentation, and conclusion or verification. These stages are carried out starting from data collection, formulation, presentation of analysis results in the form of tables to verification. The results of the study show that in the Sasak poem "Presean" by Syaiful Bahri, the most common meanings found are lexical and grammatical meanings, while figurative meanings are not found explicitly. However, based on the implied meaning, the poem describes the traditional game of the Sasak tribe which functions as entertainment as well as a form of ritual of asking for rain. This can be seen in the verse "Pinaq daraq jari ujan" (making blood rain) which is a figurative form, as if the blood that appears from the game of Presean is a symbol of asking for rain. Thus, it can be concluded that a literary work will be more interesting if it is decorated with the use of figurative words, because it can expand the meaning and enrich the aesthetic value of the work.